The Reality of Erzya-Russian Poetic Bilingualism: the Artistic Phenomenon of Alexander Arapov - Aleksey A. Arzamazov (Polylinguality and Transcultural Practices, 2022)
The article deals with the problematic and thematic projections of the work of Alexander Arapov (1959-2011), one of the most prominent representatives of modern Mordovian literature. The author focuses on the complex reality of Erzya-Russian poetic bilingualism, the study of which allows us to conclude that each of the languages has certain motive-figurative complexes, aesthetic ideas, ethno-psychological attitudes, linguo-poetic features, “voices” of traditions. So, the central place in the Russian-language poems of A.V. Arapova is occupied by existential-psychological motives, the “I”-subject analyzes the events of his life, gives them an assessment, while a negative emotional background prevails, a discrepancy between the desired and the actual is indicated. It is indicative that the theme of ethnic identity, almost obligatory for the national literature, is practically not revealed in the poems created in Russian, there are no examples of “connection” of the ethno-cultural component. One of the identified linguistic and poetic details is the representativeness of the infinitive writing. The Erzya texts analyzed by the author are far from social contexts, urban life, they have little reflection on the acutely experienced modernity. In the Erzya texts, landscape lyrics are dominant, the figurative and symbolic elements of the Mordovian ethnoculture are updated, the influence of national folklore is felt. The author’s desire for linguistic purism is noticeable in the poems in the Erzya language. Thus, it has been established that the reality of the Erzya-Russian poetic bilingualism of Alexander Arapov is not just two genetically different languages, but also two different artistic worldviews, the intersections between which are not so many.